The impact of small and medium enterprises on unemployment rates in Syria For the period ((2000-2020)) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
this study aimed to study and analyze the impact of small and medium enterprises on the unemployment rate in Syria, to present proposals that would stimulate and provide facilities for the work of these projects in Syria, in order to reduce unemployment rates and activate their role in economic development. The researcher adopted the descriptive analytical approach by describing the reality of small and medium enterprises in the Syrian Arab Republic and analyzing their impact on economic development indicators using the statistical analysis of time series. The study concluded that there is a statistically significant relationship between the number of small and medium enterprises and the unemployment rate, just as increasing the number of small and medium enterprises by one degree will reduce unemployment by 22,620 degrees, which confirms the importance of these projects in reducing the unemployment rate in Syria. Thus, increasing the number of small and medium enterprises has an effective role in economic development. Then some recommendations were presented to improve the relationship, the most important of which are: expanding small and medium enterprises and providing support in all its forms in order to increase their role in reducing unemployment rates, and supporting programs concerned with developing the small enterprise sector due to its importance in creating a new branch of work. As well as searching for maximizing the ability of the unemployed by providing support and accessing soft lending sources to provide financial support for the establishment of small and medium enterprises, reducing the unemployment rate and increasing the employment rate